3D fast map for autonomous mixed swarm robot drone (MSRD) - Ooi, Jia Min (Nanyang Technological University, 2023)
This project aims to explore the use of 3D Fast Mapping for efficient mapping of indoor environments using a Jet Racer and a Zed Mini camera. The project objectives include developing a 3D fast map imaging concept, selecting the most appropriate camera and the autonomous device as the carrier of the camera while conducting mapping, and finally, to integrate the components for fast mapping in two indoor environments. The performance of the 3D Fast Mapping approach was evaluated and compared against conventional mapping in terms of time taken to complete the map and completeness of the map produced.